Utilization of Precision Agricultural Technology in Increasing Rice Production Efficiency at PT Buyung Putra Pangan, Pemulutan, Ogan Ilir, South Sumatra Indonesia - Supli Rahim; Mukhtarudin Muchsiri; Neni Marlina; Abid Djazuli; Dian Sulistyani; Noviyadi; Andi Febriansa; Mukhlis; Oka Maris; Marwani; Nia Fitria; Dina Badriah (Journal of Smart Agriculture and Environmental Technology, 2025)
The use of Precision Agricultural Technology (PAT) is increasingly becoming the main focus in efforts to increase the efficiency of rice production in Indonesia. This research aims to identify the benefits, challenges and environmental impacts of implementing PAT on rice fields owned by PT. Buyung Putra Pangan in Pelabuhan Dalam Village, Pemulutan, Ogan Ilir, South Sumatra. The research method used is a combination of qualitative and quantitative approaches, through literature reviews from various relevant sources as well as observations and interviews in the field. The research results show that PAT has great potential in increasing the efficiency of rice production through the use of advanced technology such as soil sensors, drones for fertilization, seed dispersal, and eradication of plant pest organisms. The main benefits of PAT include increasing productivity, reducing production costs, and preserving the environment through more efficient use of inputs. However, implementing PAT in rice fields owned by PT. Buyung Putra Pangan still faces challenges, such as high initial investment costs, training requirements for farmers, and limited supporting infrastructure. Apart from that, there are also environmental impacts that need to be considered, such as the risk of soil and water contamination due to excessive use of pesticides and chemical fertilizers. Therefore, collaborative efforts are needed between the government, research institutions, the private sector and farmers to overcome these challenges and maximize the benefits of PAT in increasing the efficiency of rice production in a sustainable manner.